Active drug targeting - Erian, J.; Duerrauer, V.; Rainer, L.; Geppert, M.; Joubert, I. A.; Himly, M. (Open Schools Journal for Open Science, 2020)
Over 100 years ago, Paul Ehrlich first proposed the side-chain theory to explain how living cells mount an immune response in reaction to an infection. His theory stated that upon the encounter of a threat, cells express side-chains to bind dangerous toxins. These side-chains,cwhich he later named receptors, can break off the cell and circulate throughout the body (i.e. antibodies). Specific antibodies link to particular antigens in the same way that Emil Fischer proposed enzymes bind to their receptors, “as lock and key”. Ehrlich described these so-called “keys” or antibodies as “magic bullets”, which target toxins without harming the body. In recent years, research has focused on using antibodies not only for detection of infection, but also as aids for drug targeting. Thereby, antibodies are bound to the surface of carriers (e.g. nanoparticles) and facilitate a directed transport to a specific organ or site in the body. Aptamer- peptide- or folic acid-doped carriers furthermore have been shown to specifically target cancer cells. By using hydrophilic structures as carriers (e.g. polyethylene glycol), negative side effects esulting from the accumulation of innate proteins can be prevented. Currently, there are drug carriers in the pre-clinical development phase for the treatment of bowel cancer. Thereby, nano polymer capsules coated with a specific antibody are used to target a glycoprotein expressed on bowel cancer cells. The polymers have a size of approximately 500 nm and are produced with a so-called “layer-by-layer” procedure. Once the carrier has reached its target site, the drug needs to be released in a controlled manner. This can be facilitated, for example, by applying a magnetic field in the case of iron oxide particles. Once these particles are taken up by the cells, magnetic radiation can be used to excite the particles, resulting in the rupture of the cell and subsequent cell death.